2004
DOI: 10.1177/089686080402400407
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammation in Peritoneal Dialysis: The Search for the Holy Grail?

Abstract: Mortality and morbidity in chronic kidney disease (CKD) patients are unacceptably high. The annual mortality rate due to cardiovascular disease (CVD) is approximately 9%, which, for the middle-aged person, is at least 10- to 20-fold higher than for the general population. Classic risk factors for CVD are highly prevalent in CKD patients, but they cannot fully account for the excessive rate of CVD in this population. Instead, it has become increasingly clear that nontraditional risk factors, such as systemic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 122 publications
2
62
0
Order By: Relevance
“…The blockade of erythropoiesis from inflammation and less so from secondary hyperparathyroidism is well established and also shown in our results (25,26). In future, the usage of more biocompatible PD solutions should also be considered when studying the possible benefits in the reduction of low grade persistent (micro)inflammation and the reduction of epoetin resistance (27). In our study, the total weekly creatinine clearance and nPCR were found to have no influence on epoetin responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blockade of erythropoiesis from inflammation and less so from secondary hyperparathyroidism is well established and also shown in our results (25,26). In future, the usage of more biocompatible PD solutions should also be considered when studying the possible benefits in the reduction of low grade persistent (micro)inflammation and the reduction of epoetin resistance (27). In our study, the total weekly creatinine clearance and nPCR were found to have no influence on epoetin responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the total weekly creatinine clearance and nPCR were found to have no influence on epoetin responsiveness. Inflammation and malnutrition are closely related (25,27), and as such inflammation could be a confounder in the previously reported significant influence of nPCR on ERI (9). In contrast to a previous report (10) in which data was controlled only for TSAT, folate and vitamin B12 levels, we could find no difference in ERI for diabetic and non‐diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasised that in PD patients some specific causes of inflammation related to dialysis practice patterns (i.e. bio‐incompatibility of PD solutions, impurity of PD solutions, peritonitis and exit site infections) may also exist 64 …”
Section: Evaluation Of Elevated Crpmentioning
confidence: 99%
“…In PD, apart from systemic inflammation, intra‐peritoneal inflammation is high because of peritonitis, degraded glucose products and advanced glycation end products (Pecoits‐Filho et al . ). Systemic inflammatory markers associated with atherosclerosis such as TNF‐alpha, IL‐6 and CRP are also increased in patients on PD (Stenvinkel et al .…”
Section: Discussionmentioning
confidence: 97%